Synchronous Deglacial Overturning and Water Mass Source Changes - Roberts, N. L.; Piotrowski, A. M.; McManus, J. F.; Keigwin, L. D. (Science, 2010)
Understanding changes in ocean circulation during the last deglaciation is crucial to unraveling the dynamics of glacial-interglacial and millennial climate shifts. We used neodymium isotope measurements on postdepositional iron-manganese oxide coatings precipitated on planktonic foraminifera to reconstruct changes in the bottom water source of the deep western North Atlantic at the Bermuda Rise. Comparison of our deep water source record with overturning strength proxies shows that both the deep water mass source and the overturning rate shifted rapidly and synchronously during the last deglacial transition. In contrast, any freshwater perturbation caused by Heinrich event 1 could have only affected shallow overturning. These findings show how changes in upper-ocean overturning associated with millennial-scale events differ from those associated with whole-ocean deglacial climate events.